Intratumoral Injection of Anlotinib Hydrogel Combined With Radiotherapy Reduces Hypoxia in Lewis Lung Carcinoma Xenografts: Assessment by Micro Fluorine-18-fluoromisonidazole Positron Emission Tomography/Computed Tomography Hypoxia Imaging - Gao, Qin; Jiang, YiQing; Li, XiaoJie; Chen, Hui; Tang, Shan; Chen, Han; Shi, XiangXiang; Chen, Yue; Fu, ShaoZhi; Lin, Sheng (Frontiers in Oncology, 2021)
Hypoxia is a common feature of solid tumors that increases tumor invasiveness and resistance to radiotherapy (RT) and chemotherapy. Local application of anlotinib (AL) might increase the regulation of new blood vessel growth and improve tumor hypoxia in RT. Therefore, it is essential to fully understand the drug delivery system of AL. Herein, we applied hypoxia imaging using micro fluorine-18-fluoromisonidazole positron emission tomography/computed tomography (micro 18F-FMISO PET/CT) to assess responses to intratumoral injections of an AL hydrogel (AL-HA-Tyr) combined with RT in mice bearing Lewis lung carcinoma (LLC). We formed AL-HA-Tyr by encapsulating AL with hyaluronic acid-tyramine (HA-Tyr) conjugates via the oxidative coupling of tyramine moieties catalyzed by H2O2 and horseradish peroxidase. AL-HA-Tyr restrained the proliferation of human umbilical endothelial cells (HUVECs) in colony formation assays in vitro (p < 0.001). We established a subcutaneous LLC xenograft model using C57BL/6J mice that were randomly assigned to six groups that were treated with AL, HA-Tyr, AL-HA-Tyr, RT, and RT+AL-HA-Tyr or untreated (controls). Tumor volume and weight were dynamically measured. Post treatment changes in hypoxia were assessed in some mice using micro 18F-FMISO PET/CT and survival was assessed in others. We histopathologically examined toxicity in visceral tissues and Ki-67, VEGF-A, γ-H2AX, and HIF-1α expression using immunohistochemistry. Direct intratumoral injections of AL-HA-Tyr exerted anti-tumor effects and improved hypoxia like orally administered AL (p > 0.05), but reduced visceral toxicity and prolonged survival. The uptake of 18F-FMISO did not significantly differ among the AL, AL-HA-Tyr, and RT+AL-HA-Tyr treated groups. Compared with the other agents, RT+AL-HA-Tyr decreased HIF-1α, Ki67, and VEGF-A expression, and increased γ-H2AX levels in tumor cells. Overall, compared with AL and AL-HA-Tyr, RT+AL-HA-Tyr improved tumor hypoxia, enhanced antitumor effects, and prolonged the survival of mice bearing LLC.